2194. Hepatitis B Care Cascade Within the VA Maryland Healthcare System. (26th November 2018) - Lambing, Tyler; Tang, Lydia; Beste, Lauren A; Amoroso, Anthony; Wilson, Eleanor
Abstract: Background: Approximately 730, 000 Americans are estimated to have chronic hepatitis B (HBV) infection, but recent studies have identified gaps in HBV care. Our aim is to characterize the HBV care cascade at the Veterans Affairs Maryland Health Care System (VAMHCS). Methods: We used administrative VA data sources to identify patients enrolled at VAMHCS with a positive hepatitis B surface antigen (HBsAg) result within the VA from October 1, 1999 through February 7, 2018. Non-Veteran employees, Veterans who had died, or those with confirmed resolution of HBV infection were excluded. Chronic HBV infection was defined as a second positive HBsAg result or detectable HBV DNA >6 months later, or if included in the medical record. Resolved HBV infection was defined as undetectable HBsAg in someone with previously positive HBsAg. Results: We identified 159 patients with a history of detectable HBsAg; only 68 (43%) had confirmatory testing to verify chronic HBV infection. Most patients with confirmed HBV (90%) were male, Black (75%; 18% Caucasian, 5% Asian), with a mean age of 62 years (with standard deviation of ±12 years). Among patients with confirmed chronic HBV, 91% were seen by a provider at least once after diagnosis where HBV was addressed in the assessment and plan, 93% had e-Antigen testing, 41% had fibrosis staging (via transient elastography, liver biopsy, or FibroSure), 85% had at least one time screening for hepatocellular carcinoma (HCC), 100% had ALT testing at least once, 84% had ALT > upper limit of normal (men 30 U/L, women 19 U/L), 62% had HBV treatment at some point. Conclusion: This analysis reveals that within the Veteran population followed at the VAMHCS, less than half of those with initial detectable HBsAg have had confirmatory testing, and while the majority of patients with confirmed chronic HBV were by providers for HBV, less than half of patients received recommended fibrosis staging. More than half (62%) received treatment and the majority (84%) have had liver imaging at least once. The cascade of HBV care highlights multiple areas for targeted improvement of the care of Veterans with chronic HBV. Disclosures: All authors: No reported disclosures.